Neutrophils and Platelets as Key Players in the Pathogenesis of ANCA-Associated Vasculitis and Potential Sources of Disease Activity Biomarkers - Anna Drynda; Marcin Surmiak; Stanisława Bazan-Socha; Katarzyna Wawrzycka-Adamczyk; Mariusz Korkosz; Jacek Musiał; Krzysztof Wójcik (Diagnostics)
Anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) is a heterogeneous group of small-vessel vasculitides, characterized by the presence of antibodies binding to myeloperoxidase (MPO) and proteinase-3 (PR3) found in neutrophil granules. Apart from being the target of ANCA, neutrophils actively contribute to the vicious cycle of inflammation and vascular damage in AAV. On the other hand, platelets have recently been recognized as essential for thrombosis and as inflammatory effectors that collaborate with neutrophils, reinforcing the generation of reactive oxygen species (ROS) and the formation of neutrophil extracellular traps (NETs) in those diseases. Neutrophils exhibit morphological and functional heterogeneity in AAV, reflecting the complexity of their contribution to disease pathogenesis. Since long-term immunosuppression may be related to serious infections and malignancies, there is an urgent need for reliable biomarkers of disease activity to optimize the management of AAV. This review summarizes the current understanding of the role of neutrophils and platelets in the pathogenesis of granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA), focusing on their crosstalk, and highlights the potential for identifying novel biomarkers relevant for predicting the disease course and its relapses.